Experimental investigation of batteries thermal management system using water cooling and thermoelectric cooling techniques - Panmuang, Piyapat; Photong, Chonlatee; Soemphol, Chaiyong (Institute of Advanced Engineering and Science, 2024)
The booming electric vehicle industry seeks fast charging solutions to address the safety risks posed by high-power charging, including thermal runaway and other safety issues. This study investigates the impact of combining liquid with thermoelectric cooling on battery thermal management. A series of experiments were conducted using various thermal batteries, liquid flow rates and batteries temperature thermoelectric. The experimental results compared air cooling (AC), water cooling (WC), and thermoelectric cooling (TEC) with different water flow (WF) rate in system and revealed that TEC with WF at 4.0 l/min was the best cooling system. This system can decrease the temperature by about 41-52% from the maximum temperature at discharge rates of 1.0, 1.5, 2.0, 2.5, and 3.0 °C. However, TEC with WF 1.0 and 2.0 l/min can effectively lower the temperature and reduce energy consumption compared to other cooling systems, while still maintaining the battery temperature within appropriate ranges.